MILITARY FAMILIES STRESS AND COPING WHILE HAVING A CHILD WITH AUTISM SPECTRUM DISORDER - Dickson, Madison (East Carolina University)
This case study examined the lived experiences of a military spouse raising a child with Autism Spectrum Disorder (ASD) during periods of relocation, deployments, and reintegration. A semi-structured interview was analyzed using Colaizzi’s (1978) phenomenological method. Military related stressors, navigating autism-related services, and family resilience and adaptation emerged as the main themes. Transitions in the military cycles, relocation, deployments, and reintegration tended to disrupt care and required renewed advocacy, which was the responsibility of the military spouse. The Double ABC-X model (McCubbin & Patterson, 1983) was used to understand how stress, resources, and perceptions—specifically how families interpret or make sense of both the original stressor and the accumulation of demands over time—affect family adaptation. Informal support from other military families and personal resilience emerged as central elements to coping for this military spouse, who served as the primary parenting figure in the family. The study highlights the need for more consistent ASD services across military bases, improved provider awareness, and stronger caregiver support. Findings can inform future research, clinical practice, and policies supporting military families with children on the autism spectrum.
Keywords: Education, Physical